Ultrasound-Activated Cascade Effect for Synergistic Orthotopic Pancreatic Cancer Therapy - Cheng, Dong-Bing; Zhang, Xue-Hao; Chen, Yuanfang; Chen, Hao; Qiao, Zeng-Ying; Wang, Hao (iScience, 2020)
In some malignant tumor, especially for pancreatic tumor, poor solid-tumor penetration of nanotherapeutics impedes their treatment efficacy. Herein, we develop a polymer-peptide conjugate with the deep tissue penetration ability, which undergoes a cascade process under ultrasound (US), including (1) the singlet oxygen 1O2 is generated by P18, (2) the thioketal bond is cleaved by the 1O2, (3) the departure of PEG chains leads to the in situ self-assembly, and (4) the resultant self-assembled PK nanoparticles show considerable cellular internalization. Owing to the synergistic effect of US on increasing the membrane permeability, the endocytosis and lysosome escape of PK nanoparticles are further enhanced effectively, resulting in the improved therapeutic efficacy. Thanks to the high tissue-penetrating depth and spatial precision of US, PTPK presents enhanced tumor inhibition in an orthotopic pancreatic tumor model. Therefore, the US-activated cascade effect offers a novel perspective for precision medicine and disease theranostics. [Display omitted] •PPCs in single molecule state present remarkable solid-tumor penetrability•US induced in situ self-assembly of PPCs is verified•Assembled nanoparticles and US synergistically contribute to the cellular internalization•US-activated cascade effect leads to effective inhibition of pancreatic tumor growth Cancer; Nanomaterials; Biomedical Materials